AB1285-HPR ACCELEROMETRIC ASSESSMENT OF PHYSICAL PERFORMANCE DURING THE SIT-TO-STAND TEST IN PATIENTS WITH KNEE OSTEOARTHRITIS. (2nd June 2020) - Fellous, S.; Rkain, H.; Afilal, S.; Moulay Berkchi, J.; Fatima Zahrae, T.; Ilham, A.; Latifa, T.; Aboudrar, S.; Dakka, T.; Errguig, L.; Jniene, A.; Bakkali, M.; et al.
Abstract : Background: Knee osteoarthritis is a major public health issue that causes chronic pain and functional limitation. Objectives: This study aims to evaluate physical performance in knee osteoarthritis by clinical tests and accelerometer measurements, and investigate the relationship between physical perfomance alteration and clinical parameters. Methods: This is a cross-sectional study, included 40 patients with knee osteoarthritis (100% female, average age 57.6 ± 5.2 years, median evolution time was 36 [24, 69] months, overweight in 82.5% of patients). Clinical evaluation performed with the visual analog scale (VAS), Western Ontario and McMaster Osteoarthritis Index (WOMAC), Lequesne score, Get up and Go (GUG) and Timed up and Go (TUG) tests. The percentage of fat mass was measured using impedencemetry. All subjects were instructed to perform sit-to-stand transfers during 30 secondes. We measured the speed, strength and muscular power of the lower limbs during this test using the Myotest PRO® accelerometer. A correlation analysis was performed in search of factors associated with physical performance alteration. Results: The median speed during the sit-to-stand test was 4.3 [3.1-6.2] cm / sec. The median muscular strength and power during this test were 15.2 [13.6-17.7] Nm / kg and 14.5 [9.9-21.7] W / kg respectively. Body mass index (BMI) correlated negatively with the 3 parameters of physivcal performance mesured by the Myotest PRO® accelerometer (speed, strength and muscle power) during the sit-to-stand test (p<0, 05). There was no correlation between those measured parameters of physical performance, pain and functional indices of knee osteoarthritis. Conclusion: Our pilot study assessed the physical performance of the lower limbs in knee osteoarthritis patients, by measuring the speed, strength and muscle power during the the sit-to-stand test. It suggests an association between obesity and physical performance alteration in knee osteoarthritis patients. Disclosure of Interests: None declared